Isolation and Characterization of Endophytic Fungi Producing L-Asparaginase Enzyme from Kencur Plant (Kaempferia galanga L.) - Riyanti Djafar; Mahdalena Sy. Pakaya; A.Mu’thi Andy Suryadi; Mohamad Aprianto Paneo; Wiwit Zuriati Uno (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
L-Asparaginase is an enzyme that catalyzes the hydrolysis of L-asparagine into L-aspartate and ammonia. This enzysne has important benefits in the medical field, particularly as a biological agent is the therapy of acute lymphoblastic leukemia, due to its ability to inhibit the growth of asparagine-dependent cancer cells. This study aims to isolate and characterize endophytic fungi derived from the rhizome of the aromatic ginger (Kaempferia galanga L.) plant, and to test the ability of these isolates to produce the L-asparaginase enzyme. The research method used is an experimental method conducted in a pharmaceutical microbiology laboratory Endophytic fungi were isolated using surface sterilization techniques and culturing on PDA media. Enzyme production was performed using the submerged fermentation method, while enzyme purification used the ammonium sulfate fractionation method with concentration ranges of 0-20%, 20-40%, 40-60%, 60-80%, and 80-100%. The L-asparaginase enzyme activity test was conducted using the Nesslerization method, with Asparagus as an inducer. The results showed that several endophytic fungal isolates were capable of producing L-asparaginase, as evidenced by a brownish color in the Nessler test. The purified fractions showed varying enzyme activity at each level of ammonium sulfate saturation. Thus,endophytic fungi from the aromatic ginger rhizome have potential as an alternative source for producing the L-asparaginase enzyme, which can be further developed in the fields of pharmacy and biotechnology